Big research ideas at ILRI—Mario Herrero on the recent PLE meeting - Herrero, Mario (International Livestock Research Institute, 2011)
ILRI's Mario Herrero reflects on a recent internal 'big research ideas' competition within ILRI's People Livestock and Environment research theme.